A CASE OF TIME MANAGEMENT FOR WORKING WOMEN - Pankkhurri Semwal (Journal of International Conference Proceedings (JICP), 2018)
Time management is important in order to plan the processes and tasks in an organization . The urgency of any particular task is factor to be considered to make sure that a company is productive. When a person is productive and does progress is when he sets his mind , and is a lot more happier. For a female however the things are more tough as they manage their household responsibilities and work both. Meeting deadlines contributes to satisfaction and involves achieving a goal which has been set. It is important also because one stops doing unproductive tasks. We can detect certain groups dedicated to priority tasks ,but we can see colleagues who spend a lot of time doing unproductive tasks such as answering calls which might not be concerned with the job they are assigned. Keywords : Time management , workplace ethics, accountability, perfectionist ,satisfaction, productive, unproductive, schedule , stress, insight , solitude , commitment.